Settlement Characteristic of Warm Permafrost Embankment with Two-Phase Closed Thermosyphons in Daxing’anling Mountains Region - Guanfu Wang; Jiajun Bi; Youkai Fan; Long Zhu; Feng Zhang; Decheng Feng (Sustainability, 2022)
The Xing’anling Mountains are the second largest permafrost region in China. One of the important issues for highways in these regions is how to control the settlement during the operation period to meet the demand of road stability. This paper selects a typical permafrost embankment in the Daxing’anling Mountains permafrost region, presents the finite element models of the embankment, and verifies it using field monitoring data to study the thermal and deformation characteristics within 50 years after construction. Calculation results illustrate that the permafrost under the embankment has degraded significantly during the operation period of the highway and led to serious settlement. To prevent the degradation of permafrost, a series of models with two-phase closed thermosyphons (TPCTs) were established to analyze the cooling effect. The contribution of different factors, including install locations, depth, and shapes of the TPCTs, were assessed on their effects on cooling the permafrost and reducing the embankment settlement. Results show that the TPCTs have an excellent cooling effect on the permafrost embankment. However, as the TPCTs change the temperature distribution of the embankment, they will inevitably cause differential settlement. In order to ensure the cooling effect and reduce the differential settlement of the embankment, it is suggested that L-shaped TPCTs should be adopted in the remedial engineering.